El retrato y la representación contemporánea. - Mendoza Montesdeoca, Holmer Vicente (2017)
Portrait is defined to the graphical representation that describes the features typical of an individual, nevertheless in the contemporaneousness the extension of this concept includes towards other representations and that has to see with the symbolic thing, that is to say, that his representation is not a faithful reflection of his appearance but the image catches the essence of the being. In a beginning the boosters of the vanguardismo noticed that the painting across the mimesis had overcome any reality it targets already be across the behavior of the light or the desconstrucción of the form; the first thing is sustained in the changes that the light produces when an object is illuminated in the different phases of the day discussing even that the white is not pure, but this one was acquiring shades so much so trastocaba his purity; and the second thing, the academicismo is opposed as the only norm of representation implanted by the institution. With this precedent they propose for those who devote themselves to the portrait to think that the representation of a personage across the visual arts not always is going to be the exact copy of what one sees, more even bearing in mind that the invention of the camera it had overcome; not only it, in the current moments there exist thousands of devices that are easy to manipulate managing with it to catch or a portrait or self-portrait to be caught (selfie). With this preamble it is well-known that the art across the artists takes short-cuts very sustained in the philosophy of the art as as Danto supports across his text " The death of the art "; the author holds that they are many centuries in which the mimesis (image - illustration) had dominated the world of the art, the first thing was the symbolic thing across the Egyptian art, then the image of the religious thing and the sacred thing that was invading the mind of the christianity, finally the romanticism that I was stimulating as creative genius of the things between them the landscape.